Mobile phone MIMO antenna array miniaturization-based low SAR research in the combined EMF - Wen-Qi Hou; Yu-Xin Li; Ming-Fei Luo; Wen-Ying Zhou; Mai Lu (PLoS ONE, 2026)
Due to the diversification of media functions of mobile phones, users can make calls and access the internet simultaneously, which has significantly increased the usage time of mobile phones. The exposure dose of the users in the combined electromagnetic fields (EMF) should be further quantified to better evaluate the public exposure safety. Different from most conventional EMF safety studies that only focus on a single frequency, this work not only discusses the mobile phone simultaneously operated in fourth-generation (4G) and fifth-generation (5G) mobile communications radiation impact on users, but also verifies that the miniaturized mobile phone multiple-input multiple-output (MIMO) antenna array can significantly reduce the specific absorption rate (SAR) absorbed by users. In this article, a miniaturized mobile phone MIMO antenna array is employed as the radiation source, and multi-pose human models are established to simulate the practical utilization of a smartphone. A systematic analysis of the SAR absorbed by the human model is conducted in both single and combined EMF scenarios. The results indicate that the peak SAR in various tissues under multi-frequency exposure is 1.02 to 15.85 times higher than that under single-frequency exposure.